Asiaticoside Suppresses Gastric Cancer Progression and Induces Endoplasmic Reticulum Stress through the miR-635/HMGA1 Axis - Chao Zhang; Xiaolin Ji; Zhenguang Chen; Zhichao Yao (Journal of Immunology Research)
Objective. Gastric cancer is a prevalent malignant tumor with high morbidity and poor prognosis. Asiaticoside (AC) has antitumor effects, while its role in gastric cancer is elusive. Thus, this study investigated the effect of AC on gastric cancer progression. Methods. Cell viability and migration were determined using the CCK-8 and Transwell migration assay. Endoplasmic reticulum stress was detected through measuring the expressions of GRP78, Chop, and hnRNPA1 by Western blot. The luciferase assay confirmed the relationship between miR-635 and High Mobility Group AT-Hook 1 (HMGA1). The effect of AC on tumor growth was evaluated by establishing a xenograft tumor. The survival rate of mice was analyzed by Kaplan-Meier analysis. Results. AC suppressed gastric cancer cell viability and restrained cell migration. AC inhibited the expressions of the cell proliferation marker PCNA and EMT-related marker N-cadherin and increased E-cadherin expression. AC elevated the levels of GRP78 and Chop and suppressed the level of hnRNPA1. In addition, AC restrained gastric cancer proliferation and migration ability and induced endoplasmic reticulum stress by upregulating miR-635 expression. Furthermore, HMGA1 was proven to be a target of miR-635. AC constrained gastric cancer cell proliferation and migration and promoted endoplasmic reticulum stress by regulating HMGA1. Moreover, AC suppressed in vivo tumor growth and improved the survival time of mice. Additionally, AC elevated the expressions of miR-635, E-cadherin, GRP78, and Chop and inhibited Ki-67, HMGA1, N-cadherin, and hnRNPA1 expressions in tumor tissues of mice. Conclusion. AC suppressed gastric cancer progression and induced endoplasmic reticulum stress via the miR-635/HMGA1 axis, providing a valuable drug against gastric cancer.